A Real Anthropomorphic Gripper Controlled by a Motion Leap Device - Ionel Staretu; Catalin Moldovan (Scientific Research, New Technologies and Applications Vol. 5, 2024)
In this paper, the control of an anthropomorphic gripper with five fingers using the Motion Leap sensor is described. First, the Motion Leap device is briefly described, which can capture the movements of the fingers of the human hand and then transmit them in a virtual environment. Then the HandCommander software module and the InterfaceController application are described. The HandCommander module is created to make the connection between the human hand and the GraspIT virtual environment, and the InterfaceController application is needed to send the hand movement data to the virtual environment, further, the communication protocol is tested. For testing, a prototype of an anthropomorphic gripper with five fingers was made, with its own command and control system, which is briefly presented. The main constructive characteristics of the anthropomorphic gripper are described. The system is further tested to verify that the gestures of the human hand can be captured and transmitted to the real grasper via the virtual environment. To exemplify the effectiveness of the designed system, four cases are described, namely: grasping a tennis ball, grasping a screw spanner, grasping a mechanical shaft, and grasping a circular ball bearing. For future research, the possibility of mounting the anthropomorphic gripper on an ABB robot is described. The command of the ABB robot can be done with a Kinect device that can capture the movements of a human arm, and the command of the gripper can be done with the method described in the paper, using the Motion Leap device. A CAD simulation of a manipulation and assembly operation of two parts using this equipment is shown.